2012
DOI: 10.1177/0148607112436978
|View full text |Cite
|
Sign up to set email alerts
|

Stress Prophylaxis in Intensive Care Unit Patients and the Role of Enteral Nutrition

Abstract: Use of acid‐suppressive therapy (AST) to prevent stress gastropathy in the intensive care unit has grown rapidly over the past 20 years. The primary indications for such use of AST include need for mechanical ventilation, overt gastrointestinal bleeding, severe burn, and head trauma. Despite this limited list of indications, proton pump inhibitors (PPIs) often are overprescribed for purposes of stress prophylaxis. Decreased mucosal blood flow with subsequent tissue ischemia is thought to be the mechanism respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…They recommended that organizations use a diarrhea risk management algorithm. Hurt et al 73 suggested that incorporation of EN as a base strategy for stress ulcer prophylaxis to reduce the need for acid‐suppressive therapy may reduce C difficile pseudomembranous colitis. Others have recommended allowing stopping EN for periods of time (eg, 6‐hour break) to allow gastric pH to return to its more normal acidic pH to help reduce gastric microbial growth 44 …”
Section: Section 6 Administration: Generalmentioning
confidence: 99%
“…They recommended that organizations use a diarrhea risk management algorithm. Hurt et al 73 suggested that incorporation of EN as a base strategy for stress ulcer prophylaxis to reduce the need for acid‐suppressive therapy may reduce C difficile pseudomembranous colitis. Others have recommended allowing stopping EN for periods of time (eg, 6‐hour break) to allow gastric pH to return to its more normal acidic pH to help reduce gastric microbial growth 44 …”
Section: Section 6 Administration: Generalmentioning
confidence: 99%
“…Former surveys support that enteral nutrition is taken into consideration when evaluating the risk of stress‐related bleeding and upon commencing SUP . Current evidence is based on case reports, a limited number of serial studies in humans and several animal studies, and this explains why there is no firm evidence regarding the role of enteral nutrition in the prevention of stress ulcers . Consequently, more research into this issue is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation is one of the few indications for stress ulcer prophylaxis and acid-suppressive therapy is expected to reduce the incidence of gastrointestinal bleeding (18). The effect of mechanical ventilation on splanchnic blood flow coupled with the presence of gastric acid has been thought to increase the frequency of ulcerating lesions in the stomach (19, 20). Several adult studies have demonstrated that mechanically ventilated adults receiving pantoprazole have a higher incidence of VAP than patients receiving ranitidine (21-23).…”
Section: Discussionmentioning
confidence: 99%